The birth of Venus a novel - Dunant, Sarah (Random House Trade Paperbacks, 2004)
From its first arresting sentence, Sarah Dunant's magnificent novel embroils the reader in the coming-of-age story of Alessandra Cecchi, a fourteen-year-old girl with a strong will and a passion for painting. The Birth of Venus is a tour de force, the first historical novel from one of Britain's most innovative writers of literary suspense. Alessandra Cecchi is not quite fifteen when her father, a prosperous cloth merchant, brings a young painter back from northern Europe to decorate the chapel walls in the family's Florentine palazzo. A child of the Renaissance, with a precocious mind and a talent for drawing, Alessandra is intoxicated by the painter's abilities. But their burgeoning relationship is interrupted when Alessandra's parents arrange her marriage to a wealthy, much older man. Meanwhile, Florence is changing, increasingly subject to the growing suppression imposed by the fundamentalist monk Savonarola, who is seizing religious and political control. Alessandra and her native city are caught between the Medici state, with its love of luxury, learning, and dazzling art, and the hellfire preaching and increasing violence of Savonarola's reactionary followers. Played out against this turbulent backdrop, Alessandra's married life is a misery, except for the surprising freedom it allows her to pursue her powerful attraction to the young painter and his art. It brings alive the history of Florence at its most dramatic period, telling a compulsively absorbing story of love, art, religion, and power through the passionate voice of Alessandra, a heroine with the same vibrancy of spirit as her beloved city.